A Review on Compliant Joint Mechanisms for Lower Limb Exoskeletons. (7th August 2016) - Gálvez-Zúñiga, Miguel A.; Aceves-López, Alejandro
Abstract : Lower limb exoskeletons are experiencing a rapid development that may suggest a prompt introduction to the market. These devices have an inherent close interaction with the human body; therefore, it is necessary to ensure user's safety and comfort. The first exoskeletal designs used to represent the human joints as simple revolute joints. This approximation introduces an axial misalignment issue, which generates uncontrollable internal forces. A mathematical description of the said misalignments is provided to better understand the concept and its consequences. This review will only focus on mechanisms aiming to comply with its user.